Adaptation of Pseudomonas aeruginosa to constant sub-inhibitory concentrations of quaternary ammonium compounds. Issue 4 (28th February 2020) - Voumard, Margaux; Venturelli, Leonardo; Borgatta, Myriam; Croxatto, Antony; Kasas, Sandor; Dietler, Giovanni; Breider, Florian; von Gunten, Urs
Abstract : The susceptibility profile of P. aeruginosa exposed to constant sub-inhibitory 3 concentrations of quaternary ammonium compounds was characterized as well as the 4 nanomechanical membrane properties. Abstract : Quaternary ammonium compounds (QACs) are widely used in consumer products for disinfection purposes. QACs are frequently detected in aquatic systems at sub-inhibitory concentrations and were found to affect the development of antimicrobial resistance if bacteria are exposed to increasing concentrations. However, the effect of a constant sub-inhibitory concentration on the development of bacterial resistance is unknown. A constant exposure to 88% of the minimum inhibitory concentration (MIC) of benzalkonium chloride (BAC) led to an increase of the MIC of P. aeruginosa . It increased from 80 mg l −1 to 150 mg l −1 after 10 cycles of exposure and remained stable after removal of BAC. When exposed to cetyltrimethyl ammonium chloride (CTMA), P. aeruginosa 's MIC increased from 110 mg l −1 to 160 mg l −1 after 10 cycles of exposure and decreased to 120 mg l −1 after removal of CTMA. Additionally, cross-resistance between the QACs was observed. When exposed to BAC, the MIC for CTMA increased from 110 mg l −1 to 200 mg l −1, and when exposed to CTMA, the MIC for BAC increased from 80 mg l −1 to 160 mg l −1 . In contrast, the susceptibility to 16 antibiotics was not significantly affected by exposure to QACs. Finally, analyses of the membranes' nanomechanical properties of P. aeruginosa with atomic force microscopy (AFM) showed increases in cell roughness, adhesion and stiffness after treatment with CTMA. Since sub-inhibitory concentrations of QACs can be detected in (technical) aquatic systems including sediments, this may lead to a dissemination of bacteria with higher QAC resistance in the environment.